2010
DOI: 10.1007/s11517-010-0695-x
|View full text |Cite
|
Sign up to set email alerts
|

An expectation-maximisation approach for simultaneous pixel classification and tracer kinetic modelling in dynamic contrast enhanced-magnetic resonance imaging

Abstract: Traditionally, tracer kinetic modelling and pixel classification of DCE-MRI studies are accomplished separately, although they could greatly benefit from each other. In this article, we propose an expectation-maximisation scheme for simultaneous pixel classification and compartmental modelling of DCE-MRI studies. The key point in the proposed scheme is the estimation of the kinetic parameters (K(trans) and K(ep)) of the two-compartmental model. Typically, they are estimated via nonlinear least-squares fitting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In fact, the curvature of the model manifold is made of two contributes: the intrinsic and the parameters-effect curvature [17]. In this study, the intrinsic curvature was always zero (the model manifold is a plane embedded in the data-space), while the parameters-effect curvature was negligible for the most part of interest within the parameters space [3][4][5]9]; however, for many-parameters models this curvature effect could become important and should be considered.…”
Section: Discussionmentioning
confidence: 72%
“…In fact, the curvature of the model manifold is made of two contributes: the intrinsic and the parameters-effect curvature [17]. In this study, the intrinsic curvature was always zero (the model manifold is a plane embedded in the data-space), while the parameters-effect curvature was negligible for the most part of interest within the parameters space [3][4][5]9]; however, for many-parameters models this curvature effect could become important and should be considered.…”
Section: Discussionmentioning
confidence: 72%
“…In the last two decades, several experimental studies have demonstrated that quantitative methods (based on tracer kinetics modelling) can be more specific in distinguishing benign from malignant breast disease, because of the capability to derive parameters strictly related to tissue microvasculature without any operator dependency [19,[20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. However, as there is not yet sufficient standardisation of quantitative methods, semi-quantitative approaches have been used because they could represent a compromise between qualitative and quantitative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic curve analysis can be performed qualitatively (visual inspection of the curve shape), semi-quantitatively (by means of empirical parameters of signal intensity changes as gradient of the upslope of enhancement curves, maximum signal intensity and wash-out gradient) or quantitatively through pharmacokinetic modelling techniques [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This approach can potentially benefit from both ROI-based and pixel-by-pixel processing (Sourbron, 2010). Also, semi-automatic approaches for model-based segmentation of DCE-MRI images are currently being developed (Buonaccorsi et al, 2007;Kelm et al, 2009;Sansone et al, 2011;Schmid et al, 2006;Xiaohua et al, 2005) …”
Section: Roi Vs Pixel-by-pixelmentioning
confidence: 99%